(untitled) (Research, Society and Development, 2021)
The mental health crisis is a complex condition that requires efficient and humanized care, conceived as an expression that involves the subject’s subjective ability to respond to triggering situations at any time in life. This study aimed to consolidate scientific evidence that discusses the nursing care offered in the care of people in psychological crisis. This is a bibliographic study, integrative review type, based on primary, descriptive, exploratory studies with a qualitative and quantitative approach, through the analysis of scientific articles and theses, available in an open access electronic database. Consolidated on the premise of the six phases of the integrative review elaboration process. The articles selected for the composition of the sample were coded, and then we proceed with the synthesis of the results, grouped into two main categories, namely: Biomedical logic of psychic phenomena (mechanistic practices) and production of bond, autonomy and co-responsibility as a strategy of care. The role of nursing is permeated by limits and challenges, resulting from a troubled work process and scientific evidence in the care of the psychic crisis reaffirms the permanence of the hegemonic biomedical model, thus approaching in a reductionist way the other essential aspects of care, guided by the Reform Psychiatric. It is clear, with this study, how valuable it is to discuss about crisis, production of singularities and, above all, about nursing practices in the care of people in crisis.